2019
DOI: 10.1021/acs.jpcb.9b00922
|View full text |Cite
|
Sign up to set email alerts
|

Proteorhodopsin Function Is Primarily Mediated by Oligomerization in Different Micellar Surfactant Solutions

Abstract: The diverse functionalities of membrane proteins (MPs) have garnered much interest in leveraging these biomolecules for technological applications. One challenge of studying MPs in artificial micellar surfactant environments is that many factors modulate their structures and functionalities, including the surfactants that interact with the MP or their assembly into oligomers. As oligomerization offers a means by which MPs could selectively interact among the copious environmental factors in biological environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 54 publications
4
42
0
Order By: Relevance
“…Here, we found that the His-Asp interaction of GR becomes stronger upon monomerization and significantly increases the pKa of the Asp121 residue, which is fatal for the H + pump function. As mentioned above, a relatively small but similar pKa increase was also observed for PR upon monomerization 20,21 . Thus, the stronger His-Asp interaction might occur for both XR and PR.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Here, we found that the His-Asp interaction of GR becomes stronger upon monomerization and significantly increases the pKa of the Asp121 residue, which is fatal for the H + pump function. As mentioned above, a relatively small but similar pKa increase was also observed for PR upon monomerization 20,21 . Thus, the stronger His-Asp interaction might occur for both XR and PR.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, higher pKa narrows the pH range where the H + pump exerts the activity. The observed pKa increase was approximately 1.1 unit 21 . The resultant pKa of 7.5–7.7 is still equal to or lower than the seawater pH of 7.6–8.2 22 .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…PR pH-dependent optical absorbance change was recorded by a UV-1800 spectrophotometer (Shimadzu, Kyoto, Japan), and the data analysis for getting the pKa D97 was done by the processing and fitting algorithm described in previous studies (15). Prepared PR-containing liposomes were diluted by the HEPES buffer with the desired salt concentrations to achieve a total volume of 750 mL and an initial optical density between 0.3 and 0.5 at 520 nm.…”
Section: Optical Absorption Measurements and Analysesmentioning
confidence: 99%
“…Moreover, the pKa of embedded residues was also shown to be affected by the environment in which the TMP resides. For example, the pKa of the embedded D97 residue (pKa D97 ) of PR can differ by more than one unit by the extent of oligomerization of surfactant-reconstituted PR (14,15), as well as the NaCl concentration in the buffer that contains detergent-constituted PR (16). These results unveiled that the external environment in which TMP resides can affect the pKa of embedded charged residues, but not the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%